Evaluasi Kinerja Struktur Baja PT Mega Lifesciences Indonesia Menggunakan Analisis Pushover - Puja Anggara Pratama; Dea Yunita Sari (LPPM Universitas Sangga Buana, 2025)
This study evaluates the structural performance of a five-story production building of PT. Mega Lifesciences, consisting of a steel frame system with a reinforced concrete roof slab, located in Bogor City. The building is classified as risk category II with a soft soil site class. Seismic analysis was carried out using the response spectrum method in accordance with SNI 1726:2019, while the structural performance evaluation was conducted through nonlinear static pushover analysis using the FEMA 440 Equivalent Linearization procedure based on ASCE 41-23. The objective of this research is to determine the performance level of the building by identifying the plastic hinge formation mechanism in bracings, beams, and columns, as well as examining the relationship between base shear and displacement in the pushover and seismic demand curves. The pushover analysis results indicate that in the X direction, the structure reaches a performance point classified as Damage Control at the coordinate (V; D) = (22,724.51 kN; 85.87 mm), while in the Y direction, the performance point is obtained at (V; D) = (24,400.23 kN; 71.19 mm). These findings indicate that the structure experiences damage but remains capable of maintaining its stability under seismic loading.